Development and validation of breast cancer knowledge and beliefs questionnaire for Malaysian student population - Zavare, Mehrnoosh Akhtari; Aliyan-Fini, Fatemeh; Baghestan, Abbas Ghanbari; Mohd Sidik, Sherina (Universiti Putra Malaysia Press, 2018)
This study aimed to develop and validate a questionnaire on Malaysian students' knowledge and belief toward breast cancer and breast cancer screening. A cross sectional study was conducted among 792 female undergraduate students in selected public universities in Klang Valley, Malaysia. Convergent and discriminant validity tests were used for assessing construct validity of the questionnaire while the internal reliability of the instrument was checked by Cronbach's alpha. The average age of respondents was 22 years (21.77± 1.20). Majority of them were single (96.8%), Malay (91.9%), and Muslim (94.6%). This instrument had a good face and content validity. Cronbach's alpha coefficient for Health Belief Model Scales ranged between 0.73-0.83, indicating acceptable levels of internal consistency. The Kappa value for the knowledge part ranged between 0.52-0.90, also showing acceptable reliability. The developed instrument indicated good construct validity and reliability for Malaysian female students. This instrument can help health care planners and providers to measure levels of knowledge and beliefs of Malaysian women toward breast cancer before planning appropriate intervention.